STUDY OF THE COST FORMATION CHARACTERISTICS OF HYDROCARBON OUTPUT AND THEIR ACCOUNTING RECOGNITION - Khoma, Svitlana; Savchuk , Tetyana; Kostyuk , Ulyana (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The main elements of the cost management system of oil and gas production are its accounting and calculation and consideration of the technological process stages. The article analyses the formation features of production costs at oil and gas production enterprises; it also determines the effect of organizational and technological features of oil and gas production enterprises on the production costs structure. The specific nomenclature of cost estimates of oil and gas production departments will improve the current cost accounting, cost formation control and prevent the irrational and inefficient use of material, labor and financial resources for oil and gas production. It was determined that the list and composition of calculation items of oil, natural gas and associated gas production cost depend on the economic homogeneity, combined in the items, production organization, diversity of technological processes, the possibility of direct or reasonable indirect attribution of expenses to production cost. It was studied, that oil and gas production process is arranged as follows: at the end of several process stages a semi-finished product is produced (crude oil, oil gas, natural gas, unstable gas condensate); the finished product (commodity oil, commodity gas, stable gas condensate) is produced at the end of the last technological process to prepare the semi-finished product according to state standard requirements. The nomenclature of calculated cost items, including specifics of the formation of hydrocarbon production cost was systematized. In contrast to the current practice, it will increase awareness of involved users to identify the reduction mechanisms of production costs.